PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA LAUNDRY BREE CLEAN SEKAYU - Ade Nia Suryani; Neti Erlina (Jurnal Manajemen Kompeten, 2021)
This study aims to determine the effect of service quality on consumer satisfaction at Sekayu Bree Clean Laundry. This research is a study of causality. The population of this research is all consumers of Bree Clean Laundry in Sekayu City, in which the sample amounted to 89 people. The total sample was determined using the Slovin formula. The sample was selected using accidental sampling technique. Data were collected using the questionnaire method and analyzed using simple linear regression analysis and correlation analysis. The coefficient of correlation (R) value of 0.317 indicated that there was a low correlation between the service quality and consumer satisfaction at Sekayu Bree Clean Laundry, while the coefficient of determination (R Square) value of 0.100 indicated that service quality only affected 10% of consumer decisions. Keywords: Service Quality, Consumer Satisfaction, Bree Clean Laundry, Regression Analysis, Correlation Analysis